Impact of Multimorbidity on Symptoms of Depression, Anxiety, and Stress in Older Adults: Is There a Sex Difference? - Lin, Huang; Xiao, Shujuan; Shi, Lei; Zheng, Xiao; Xue, Yaqing; Yun, Qilong; Ouyang, Ping; Wang, Dong; Zhu, Hong; Zhang, Chichen (Frontiers in Psychology, 2021)
Introduction: Multimorbidity has become a key issue in the health care sector globally, and it can also lead to psychological distress in older adults. This study aimed to assess the impact of multimorbidity on depression, anxiety, and stress symptoms and identify whether there is a sex difference in these associations. Methods: A cross-sectional study using a multistage random sampling method was conducted among 3,266 older adults in China. Multiple linear regression models were used to estimate the independent associations between multimorbidity and depression, anxiety, and stress symptoms. Furthermore, interaction analysis was employed to investigate the interaction effect of multimorbidity and sex on depression, anxiety, and stress symptoms. Results: A total of 3,250 participants aged 60 years and older were included in this study. Our findings suggest that multimorbidity is strongly positively associated with depression, anxiety, and stress symptoms. In addition, the positive relations between multimorbidity and depression, anxiety, and stress symptoms are stronger for older female than male adults. Conclusion: Old adults with multimorbidity are more likely have depression, anxiety, and stress symptoms. This study offers new insight for the mental health from the perspective of multimorbidity among older people, implies that encouraging the accessibility of treatment for multimorbidity in older people with different sex may be effective in promoting mental health in China.